A POSSIBLE REASON OF FORMING THE VARIOUS TYPE OF SPECTRA IN EXTRAGALACTIC OBJECTS - Kovalev, Yu. A.; Kovalev, Y. Y. (Одеські астрономічні публікації, 2017)
An analysis of multifrequency observations of 1,300 instantaneous spectra at cantimeter-decimeter waves during 7 sets for a sample of up to 200 VLBI-compact objects gives a strong experimental evidence to an old hypothesis, that a VLBI-compact jet of relativistic particles from an object's nucleus is a main reason of forming the various type of spectra inextragalactic objects. It is enough to explain all main known spectra types (steep, flattened, inverted) by two spectra components only- of a quasi stationary jet in a longitudinal magnetic field and an optically thin cloud or envelope, resulted by the jet. A combination of thesetwo components gives also complex shapes in a case of a nonstationary phase of the jet.